A Two-Agent Model of Inflation - Frank Browne; David Cronin (Credit and Capital Markets – Kredit und Kapital, 2018)
Models of inflation usually have monetary policy affecting the economy through either an interest rate channel or a monetary/credit quantity channel but not through both simultaneously. It is argued here that policy is transmitted via two distinct types of agents – those that are and that are not liquidity-constrained. The implication is that both interest rate and monetary channels must be seen as complementary, joint indicators of inflation and must both be incorporated into models of inflation. A formal representation of price level determination and behaviour in this two-agent framework is provided and evaluated econometrically using US data. – – Ein Zwei-Agenten-Inflationsmodell In Inflationsmodellen wird üblicherweise angenommen, dass die Geldpolitik auf die Wirtschaftsleistung entweder durch den Zinskanal oder durch die Geldmenge/Kreditmenge wirkt, jedoch nicht simultan durch beide Kanäle. Hier wird argumentiert, dass die Geldpolitik auf zwei verschiedene Typen von Agenten wirkt – liquiditätsbeschränkte und nicht-liquiditätsbeschränkte. Dies hat zur Folge, dass sowohl der Zinskanal, als auch der Geldmengenkanal als komplementäre Indikatoren der Inflation angesehen werden können und gemeinsam in einem Inflationsmodel berücksichtigt werden müssen. Es wird eine formale Darstellung des Preislevels sowie des Verhaltens der Agenten in einem solchen zwei-Agenten Framework dargestellt und ökonometrisch mit US Daten untersucht.
Keywords: E31; E41; E51; E52; 330; inflation; monetary policy; liquidity constraints